Chiesa-Cristo. Il valore cristologico delle immagini ecclesiali nel Magistero primario di Papa San Paolo VI - Cigna, Sabina (Alpha omega, 2022)
In this work it is demonstrated how the ecclesiology of Pope St. Paul VI is eminently Christocentric. This has been done taking into consideration only his primary magisterium (encyclical letters and apostolic exhortations) within which the images with which Paul VI speaks of the Church following an order of frequency ranging from major to minor were analyzed. These images are certainly not new, but the way in which Paul VI used them is new in the sense that they can only be understood starting from a fundamental concept of his ecclesiology according to which the Church is Christ, it is the sacrament of Christ who is its divine animating principle. Not only that, but these images also constitute a program of life that he wanted to give to the Church and that he lived personally. Only on the basis of this awareness could she bring about her renewal and come out to meet humanity.